Evaluation of Nutritional Assistance Education Models: A Systematic Review - Rusmimpong Rusmimpong; Asni Johari; Intan Intan; Guspiyanto Guspiyanto (Iran University of Medical Sciences, 2022)
Background: The establishment of good eating practices that begins in infancy will impact lifelong nutritional habits and overall health. This study evaluates effective educational models to increase parents' knowledge and awareness in the field of nutritional assistance to toddlers through published articles from 2010 to 2021. Methods: PubMed, ScienceDirect, Web of Science, Cochrane, and Wiley online library were searched according to PRISMA (Preferred Reporting Item for Systematic Reviews and Meta-analysis) guidelines to identify published studies from January 2010 to December 2021 based on the inclusion and exclusion criteria. Two authors independently extracted the related data. The extracted data were synthesized thematically by collecting the main findings, the design, and the applied interventions. The quality of the included articles was assessed using the EPHPP (quality assessment tool of the Effective Public Healthcare Panacea Project) and the McMaster critical appraisal tool. Results: Search results from five databases yielded 842 related articles. However, only 7 articles met the inclusion criteria. The number of participants in these studies varied from 20 to 300 mothers of toddlers. The study designs included randomized controlled trials, quasi-experimental, cross-sectional, and qualitative.   Home talks, nutrition education, and counseling were the educational methods used. The duration of the intervention varied from 2 weeks up to 9 months. Home talks seem to be a more effective method with direct (teacher-directed), interactive (discussion, sharing), and experiential (learner-centered, activity-oriented) delivery methods. Conclusion: Three of the 7 studies had strong quality, and the rest had moderate quality. The evidence presented in this review has identified characteristics that may contribute to the effectiveness of interventions in increasing parents' knowledge and awareness of nutritional assistance for toddlers. The overall result from this review reveals the need to improve the standards and procedures in intervention design and randomized controlled trials to improve their effectiveness.